2018
DOI: 10.3390/ijerph15040602
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fine Particulate Matter and Associated Health Burden in Nanjing

Abstract: Particulate matter (PM) air pollution has become a serious environmental problem in Nanjing and poses great health risks to local residents. In this study, characteristics of particulate matter with an aerodynamic diameter less than 2.5 μm (PM2.5) over Nanjing were analyzed using hourly and daily averaged PM2.5 concentrations and meteorological parameters collected from nine national monitoring sites during the period of March 2014 to February 2017. Then, the integrated exposure-response (IER) model was applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 43 publications
1
23
0
1
Order By: Relevance
“…The attributable fractions (AFs) of the ∆Mort attributable to PM 2.5 exposure in Hefei are 48% (44%), 32% (29%), 32% (26%), and 25% (21%) for STR, IHD, LC, and COPD in 2014 (2015), respectively ( Supplementary Table S1). Similar to previous studies, a particularly strong correlation is revealed between excess STR mortality and PM 2.5 exposure [48][49][50][51]. With reducing PM 2.5 concentrations, the avoidable ∆Mort caused by different diseases decreases correspondingly (Figure 9).…”
Section: Health Burdens Attributed To Pm 25 Exposuresupporting
confidence: 86%
“…The attributable fractions (AFs) of the ∆Mort attributable to PM 2.5 exposure in Hefei are 48% (44%), 32% (29%), 32% (26%), and 25% (21%) for STR, IHD, LC, and COPD in 2014 (2015), respectively ( Supplementary Table S1). Similar to previous studies, a particularly strong correlation is revealed between excess STR mortality and PM 2.5 exposure [48][49][50][51]. With reducing PM 2.5 concentrations, the avoidable ∆Mort caused by different diseases decreases correspondingly (Figure 9).…”
Section: Health Burdens Attributed To Pm 25 Exposuresupporting
confidence: 86%
“…It is known that a wide range of adverse health outcomes including asthma, respiratory disease, cardiovascular disease, lung cancer ( Cascio and Long 2018 ; Fuertes et al 2020 ; Guo et al 2019 ; Knibbs et al 2018 ; Rodriguez-Villamizar et al 2015 ; Sun et al 2019 ), etc., are associated with air pollution. While great efforts in recent years have been made to reduce air pollution in particularly fine particulate matter (PM 2.5 ) concentration, China is still suffering relatively heavy air pollution and potentially high health risks particularly in densely populated regions ( Nie et al 2018 ; Sahu et al 2020 ; Shen et al 2017 ; Shen et al 2020 ). Haze events still occurred due to that enhanced production of secondary aerosol components might compensate the reduced primary emissions ( Chang et al 2020 ; Huang et al 2020b ; Le et al 2020 ; Sun et al 2020 ; Wang et al 2020a ), yet an overall improvement of air quality was very probably during COVID-19 period ( Bao and Zhang 2020 ; Huang et al 2020a ; Shi and Brasseur 2020 ; Xu et al 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al explored the spatiotemporal variations of six criteria air pollutants and influencing factors (sources and meteorology conditions) in the city clusters of the Sichuan Basin, which are located on the upper reaches of the YREB, and the results indicated that both PM 2.5 and O 3 were simultaneously high in the West Sichuan Basin while PM 2.5 in the South Sichuan Basin was much higher than that in other regions [ 17 ]. Numerous joint studies on particulate and gaseous pollutants have been carried out in representative urban cities in the Yangtze River Delta region, located on the down reaches of the YREB, such as Shanghai and Nanjing [ 18 , 19 , 20 , 21 ]. In our earlier study, concentrating on three metropolises in the YREB, we checked the current air pollution status in Chongqing, Wuhan, and Nanjing and compared the results with earlier peer-reviewed studies [ 22 ].…”
Section: Introductionmentioning
confidence: 99%